2021
DOI: 10.3389/fpubh.2021.745545
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, Social Support, Illicit Drug Use, and Other Predictors of Anxiety and Depression Among HIV/AIDS Patients in Pakistan: A Cross-Sectional Study

Abstract: Introduction: Anxiety and depression in people living with HIV/AIDS (PLWHA) can lead to non-adherence to antiretroviral therapy (ART), morbidity, and mortality. Therefore, assessing the stigma, social support, and other determinants of anxiety and depression in PLWHA are important for developing further interventions.Methods: An institution-based cross-sectional study was conducted in 505 PLWHA, approached through systematic sampling, who paid routine visits to the ART center, Pakistan Institute of Medical Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 64 publications
(95 reference statements)
0
8
0
Order By: Relevance
“…We found that “not feeling cheerful” and “not feeling relaxed” were the bridge symptoms in the depression and anxiety clusters, which indicated that these symptoms could serve as bridges between clusters. In complex networks, bridge nodes are essential for calculating the co-occurrence of clusters [ 26 ]. This result is noteworthy because a large number of PLWH may have both depressive and anxious symptoms at the same time due to stigma, intolerance of uncertainty, fear of death, and medications.…”
Section: Discussionmentioning
confidence: 99%
“…We found that “not feeling cheerful” and “not feeling relaxed” were the bridge symptoms in the depression and anxiety clusters, which indicated that these symptoms could serve as bridges between clusters. In complex networks, bridge nodes are essential for calculating the co-occurrence of clusters [ 26 ]. This result is noteworthy because a large number of PLWH may have both depressive and anxious symptoms at the same time due to stigma, intolerance of uncertainty, fear of death, and medications.…”
Section: Discussionmentioning
confidence: 99%
“…However, after B-CBT treatment, participants perceived a signi cant positive change in social support [57,58]. When we educate the patients and train them through role plays, they try to look forward in social context, improve their social support system, and talk with others comfortably; they reduce their stigma and depression [59,60]. Increasing social support among patients improves the quality of life…”
Section: Discussionmentioning
confidence: 99%
“…12 Current studies have also suggested that the prevalence of depression among HIV/AIDS patients could be higher in low-and middle-income countries compared with high-income countries, 13 ranging from 47% in the US 14 to 80% in Pakistan. 15 To be noted, initiative evidence from China has indicated that the prevalence of depressive symptoms is 74.2% among older adults with HIV/AIDS, 16 significantly higher than that among the general HIV/AIDS population (53.8%). 17 As one of the most common mental illnesses worldwide, depression has affected approximately 121 million people.…”
Section: Introductionmentioning
confidence: 98%